Assessment of the Effectiveness of Commodity Mutual Funds During the COVID-19 Pandemic: On the Example of Poland and Hungary - Agnieszka MOSKAL (Communications of International Proceedings, 2021)
The turmoil on the financial markets during the COVID-19 pandemic resulted in an increased interest in investments with exposure to commodity markets. Over the past year, the prices of many commodities have reached their highest levels in years, and even in history. This study is an attempt to verify the extent to which the situation on the commodity markets translated into the evaluation of the effectiveness of commodity mutual funds. For this purpose, the effectiveness of commodity mutual funds in Poland and Hungary in the period 2016-2020 was analyzed, divided into precious metals funds and mixed commodity funds. Both simple measures and risk-adjusted factors such as Sharpe, Treynor, Jensen's alpha, Information ratio, M2 or Sortino were used to assess the effectiveness of commodity funds. The obtained results indicate that in 2020, commodity mutual funds, both in Poland and in Hungary, were characterized by the highest level of total and systematic risk in the analyzed period. Despite the increased level of risk, most commodity funds with strong exposure to gold prices and other precious metals have managed to generate excess returns. On the other hand, managers of commodity funds with a more diversified investment strategy and greater portfolio diversification were not able to obtain a satisfactory premium for the risk taken. These conclusions are consistent with the trends that can be observed in 2020 on the markets of individual commodities.
Keywords: Performance Evaluation; Commodity Mutual Funds; Commodities; Investment Performance During COVID-19; Effectiveness of Mutual Funds; Risk-Adjusted Measures